The role of islamic religion teachers in fostering adab of students at SMP Sebelas Maret Bandung City - Hermawanto, Andi; Maharani, Nurma Yunia; Rusdiani, Ani; Nurjaman, Deden; Umam, Hoerul (ARKA INSTITUTE, 2024)
This research aims to find out the role of Islamic religious education teachers in developing students' etiquette at Sebelas Maret Middle School, Bandung City, the efforts of Islamic religious education teachers in developing students' etiquette at Sebelas Maret Middle School, Bandung City and the students' etiquette at Sebelas Maret Middle School, Bandung City. In this research, the author used descriptive analytical methods. This is a method that functions to describe or provide an overview of objects through data or samples that have been collected from data analysis techniques with data collection procedures using observation, interviews and documentation. Interviews in this research were conducted with 2 Islamic religious education teachers, and 14 students representing classes VII, VIII and IX. The results of this research indicate that Islamic religious education teachers have played an active role in developing students' manners at Sebelas Maret Middle School, Bandung City. This can be seen from the efforts carried out by Islamic religious education teachers at Sebelas Maret Middle School, Bandung City, especially Islamic religious education teachers who are intensive every day and every week, such as familiarizing themselves with tadarus Qur'an, pearls of wisdom, reciting Asmaul Husna, midday prayers in congregation. They also read and write the Qur'an by heart. The manners of students at SMP Sebelas Maret Bandung City are also categorized as quite good.